Fermentation of Tambelo and its product characteristics - Lely Okmawaty Anwar; Linawati - Hardjito; Desniar - - (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
Tambelo (Bactronophorus sp.) is a wood borer grouped into mollusc and living in the mangrove logs that have died and suffered from decaying process. Regarding empirical experience of the coastal people of Southeast Sulawesi and some research, it indicates that tambelo has a high nutrition which is so beneficial for human’s health. Tambelo is highly perishable and the usage of it is hardly found so the consumption level is low, therefore fermenting the tambelo is the right way. The objectives of this research are to make fermentated tambelo by using bakasang as a starter and to determine the quality of final product.The value of pH, NaCl concentration, total bacteria, and total lactic acid bacteria (LAB) every week for 4 week were analyzed during fermentation, then the quality of final product were determined based on chemical composition and amino acids. During fermentation pH and NaCl concentration decreased however total bacteria and total lactic acid bacteria (LAB) increased in to two weeks then decreased until the fourth week. Tambelo fermentation has a total protein contents which is higher than the total protein of fresh tambelo and fermentation proses was run perfectly although the level are lower than the total amino acid compotition in fresh tambelo.Keywords: fermentation, mangrove, tambelo